Unit trust performance measurement: the snail trail approach - Tan, Yen Keng (Universiti Putra Malaysia Press, 2000)
Unit trust is an investment scheme that offers investors a well diversified portfolio managed by a professional fund manager or organisation. The investment horizon is medium to long term depending on the stipulated objective of the unit trust. Due to the long holding period and compounding effect, a slight difference in the annual rate of returns can be very detrimental to the investor. Therefore the performance of a unit trust as well as the fund manager must be carefully evaluated before committing to the fund. As we know, a high rate of returns in a single period can be very misleading if we do not study the volatility of the historical returns. Risk adjusted returns offer a solution to this problem, but this is only a "snapshot" performance measurement analysis. Snail-Trail analysis was introduced to overcome these drawbacks and better portray the dynamic history of fund manager's performance. 17 equity growth funds were selected for the purpose of this study. From the snail-trail analysis, two promising unit trusts were found to be Asia Progress and KLMF Growth. Both funds have shown improvement in relative performance from the "high return high risk" and "low return low risk" quadrant moving up to "high return low risk", the most favourable, quadrant. Meanwhile, three funds have been classified as below average as the snail trail diagrams shown deteriorating performance. These three funds are BHLB High Growth, KLMF Industry, and KLMF Aggressive Growth, the performance of which has been falling rapidly over recent years,from the "high return low risk" quadrant to "low return high risk" quadrant. Four unit trusts showing the most consistency in fund risk-return performance are SBB Premium Capital, HLB Growth, OSK Equity and RHB Capital.